ҚЫТАЙ ТІЛІНДЕГІ АСТАРЛЫ СӨЗДЕР - Қалиқан, Ә. (Journal of Oriental Studies, 2016)
Китайский язык относится к китайско-тибетскойсемье языков, распадается на 7 основных диалектныхгрупп: северную (свыше 70% говорящих), У, Сян,Гань, Хакка, Юэ, Минь. Диалекты различаются фоне-тически, что затрудняет или делает невозможным меж-диалектическое общение, лексикой, отчасти граммма-тикой, однако основы их грамматического строя и сло-варного состава едины. Диалекты связаны регулярнымизвуковыми соответствиями.Allegorical saying features of jargon. A set phraseexpresses a specific concept using fixed constituents. Theseare often proper nouns, technical terms, and idioms. Forexample. Idioms-The Chinese language has many idiomswhose meaning is not clear from the meaning of itsindividual words and which must be learnt as a whole unit.A great number of them (especially those that originatedfrom the ancient Chinese) take the form of four charactersto show a beauty in rhetoric.Abbreviations- A Chinese abbreviation is the shortenedform of a phrase. In general, it is formed by using the firstor key characters (syllable) of every or key words in phrase,The set phrases include idioms and abbreviatedexpressions.